Back stepping-Based-PID-Controller Designed for an Artificial Pancreas model - Mohammad Ridha, Taghreed M.; Kadhum, Mina Qais; Mahdi, Shaima Mahmou (Al-Khwarizmi Engineering Journal, 2011)
Artificial pancreas is simulated to handle Type I diabetic patients under intensive care by automatically controlling the insulin infusion rate. A Backstepping technique is used to apply the effect of PID controller to blood glucose level since there is no direct relation between insulin infusion (the manipulated variable) and glucose level in Bergman’s system model subjected to an oral glucose tolerance test by applying a meal translated into a disturbance. Backstepping technique is usually recommended to stabilize and control the states of Bergman's class of nonlinear systems. The results showed a very satisfactory behavior of glucose deviation to a sudden rise represented by the meal that increase the blood glucose